Designing WebRTC Video Communication Based SDN Approach for Low latency (International Journal of Engineering and Computer Science, 2025)
To offer Quality of Service (QoS) for real-time collaborative video applications like video conferencing and distance learning, the network must select the optimal path among several choices. There might be other network paths that link the source and the endpoint, but it is difficult to avoid low latency by taking a different path due to the network's tight coupling and complex architecture. As long as network topologies such as Integrated Services (ISs) install the path selected by the routing protocol, it may not offer optimal performance. The main aim of this paper is to build and implement interactive video in real-time and find out the QoS using Python language and Web Real-Time Communication (WebRTC) technology with Software-Defined Networking (SDN) for selecting network architecture to obtain the best route based on a network-wide perspective. Besides, it has demonstrated the outcomes of the best route and assesses the performance. Not only that but also, this work presents a new technique using WebRTC with SND to obtain better paths with low latency.